Habitat utilization of the Sumatran rhinos (Dicerorhinus sumatrensis harrissoni) in Kutai Barat forest, East Kalimantan, Indonesia - MUKHLISI MUKHLISI; TRI SAYEKTI NINGSIH; ULFAH KARMILA SARI; YUYUN KURNIAWAN; RIDWAN SETIAWAN; AHMAD MUSLIM (Biodiversitas Journal of Biological Diversity, 2018)
Mukhlisi, Ningsih TS, Sari UK, Kurniawan Y, Setiawan R, Muslim A. 2018. Habitat utilization of the Sumatran rhinos (Dicerorhinus sumatrensis harrissoni) in Kutai Barat forest, East Kalimantan, Indonesia. Biodiversitas 19: 1842-1850. Sumatran rhino population in Kutai Barat forest faces a high threat of extinction. Conservation efforts can be developed more effectively and efficiently by understanding the condition of their natural habitat. This study aimed to analyze various factors influencing habitat utilization of the Sumatran rhino in Kalimantan, specifically in Kutai Barat forest. We used past survey data of rhino presence carried out by WWF from 2014 to 2016. GPS coordinates were recorded for all signs of rhinos, such as camera trap images, footprints, bites mark on food plant, dung piles, urine, scratch, twisting, and lying signs. Rhino occurrence GPS coordinates were plotted on a map of the Sumatran rhino's habitat distribution in Kutai Barat using a grid of 2 x 2 km2 size. Spatial analyses were run using ArcGIS 10.6. We used a habitat selection index formula to analyze habitat preference and biner logistic regression to develop Resources Selection Function (RSF). We found that the preferred habitat of the Sumatran rhino was in the secondary forest with medium and high vegetation densities. The most influential habitat variables on the presence of Sumatran rhinoceros in the Kutai Barat forest were the slope and distance from wallow. The Sumatran rhinoceros were more likely to be found in the sloping areas and the areas closer to the wallows.